Dividend Policy And Stock Price: Testing The Miller-Modigliani Dividen Irrelevant Theory LQ45 In Indonesia - Nababan, Boy Chandra; Isfenti Sadalia; Prasetya, Muhammad Dimas; Nurul Adelia (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The dividend irrelevance theory proposed by Miller and Modigliani suggests that dividend policy does not affect firm value in a perfect market with no transaction costs and taxes. However, this theory has been widely debated in empirical research, with mixed results across different stock markets. This article aims to test the validity of the dividend irrelevance theory in Indonesia by examining companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) for the period 2019-2023. The methodology includes analyzing stock prices before and after dividend announcements, considering the impact of transaction costs and taxes. The findings indicate that the dividend irrelevance theory does not fully apply in Indonesia, as significant differences were observed between stock prices before and after dividend announcements. This suggests that dividend policy remains relevant for investors in the Indonesian stock market.